The effects of situational factors on the choice of the mechanical engineering expertise program in Vocational High Schools - Dwi Rahdiyanta (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2017)
The objective of this study was to determine the effects of the family environment, the previous school environment, the social environment, and the students' attitude on the choice of the mechanical engineering expertise program in Vocational High Schools (VHSs) by the graduates of Junior High Schools. This was a correlational study which was ex post facto in nature. The study population totaled 1095 students. The sample, consisting of 300 students, was selected using the proportional random sampling technique by means of the Krejcie and Morgan formula. The data were collected through inventories, observation sheets, and documents. The content validity was assessed through expert judgment. The construct validity was assessed using the factor analysis and the reliability using the Cronbach's Alpha formula. The data were analyzed using the descriptive analysis, regression analysis, and path analysis at a significance level of 0.05. The results showed that, there were significant effects of the family environment, the previous school environment, the social environment, and attitude in the choice of mechanical engineering expertise program in VHSs by the graduates of Junior High Schools